Financial Management Application Design and DevelopmentAndroid Based (Case Study: Undergraduate Students of Pahlawan Tuanku Tambusai University) - Maswir, Adam Winanda; Marwa, Safni; Setiawan, Beny (Journal of Engineering Science and Technology Management (JES-TM), 2026)
Personal financial management is a crucial aspect of maintaining financial stability, especially for students who often face financial constraints and difficulty recording daily transactions. This study aims to design and build anAndroid-based financial management application using the Flutter framework and Firebase as a database. The research method used was a prototype method, consisting of requirements gathering, system design, prototype creation, user evaluation, implementation, and testing. Data was obtained through interviews and observations with students at Pahlawan Tuanku Tambusai University, Bangkinang Kota District, Kampar Regency, Riau, many of whom still lack good financial record-keeping habits. The developed application provides features for recording income and expenses, budget planning, graphical financial reports, and fund allocation notifications. Black-box testing results indicate that the application meets user needs, is easy to use, and can help students track their finances more effectively and efficiently. Therefore, this application is expected to be a practical solution for improving financial literacy and student financial management habits.